If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 5 + 7 = 13 Reorder the terms: 5 + 7 + X = 13 Combine like terms: 5 + 7 = 12 12 + X = 13 Solving 12 + X = 13 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + X = 13 + -12 Combine like terms: 12 + -12 = 0 0 + X = 13 + -12 X = 13 + -12 Combine like terms: 13 + -12 = 1 X = 1 Simplifying X = 1
| t/8=5 | | X+(6+x)+(x-3)=27 | | x(x+1)=xy-15 | | 12x+12x=180 | | 2.5-.50y-y=1 | | 2x^2-6ix+8=0 | | 8(v+3)-4v=2(2v+4)-11 | | 6(x+8)=24+3(y-5) | | 4-4b=x | | 1.01(1.27)(8-x)=10 | | 17=2x+6x-6+7 | | -n+-39=-5(1+7n) | | 12x+12x+1=90 | | 15,8/x=0.7 | | 10(v+2)-4v=2(3v+2)-13 | | 3(4K-1/3)=12k | | x+(x+1)=15+xy | | 12x+12x=90 | | 3(4K-1/3)=12 | | 12x+12=90 | | 10k+17=-83 | | 10+10+4=2x+2x | | 15(y-6)-12(y+4)=21 | | 1/3x-1/4(x-7)=4x | | a+24=16 | | 60y=360 | | -12z^5+14z^4+10z^3= | | 5x+91-2x=x | | 10a-16=3a+5 | | 1.2(f-4)=-16.8 | | 9m-18=40m | | 4(7)(x)=252 |